Effects of exercise on netrin-1 and TNF-α levels in non-inflammatory conditions (Annals of Medical Research, 2021)
Aim: Exercise has been shown to increase netrin-1 expression and decrease TNF-α response in inflammatory conditions. However, the effect of exercise on netrin-1 and TNF-α levels in non-inflammatory conditions has not yet been explicated. The objective of this study was to investigate the effect of exercise on netrin-1 levels in relation to TNF-α.Material and Methods: The exercise group (n=6) consisted of 6 male Balb-c mice that were kept in cages with access to a running wheel for 6 weeks. The control group (n = 6) was kept in cages without a running wheel for the same time period. At the end of 6 weeks, both groups were sacrificed. Netrin-1 and TNF-α levels of the muscle, brain, and kidney tissues were measured.Results: Netrin-1 and TNF-α levels were not different between the two groups in all tissues. Netrin-1 and TNF-α levels were correlated in the brain, muscle, and kidney tissues of the exercise group and the muscle and kidney tissues of the control group.Conclusion: In non-inflammatory conditions netrin-1 and TNF-α levels are correlated in muscle and kidney tissues but not in brain tissues. Exercise does not affect netrin-1 and TNF-α levels of muscle and kidney tissues but induces a correlation between netrin-1 and TNF-α levels of brain tissue.
Keywords: Exercise; netrin-1; TNF-α; muscle; brain; kidney